(untitled) (Acta Polytechnica CTU Proceedings, 2017)
The hardest tissue in the human body is the enamel which covers the anatomical crowns of teeth. It must be resistant to mechanical stress and the chemical attack of many substances from food, drinks and products of the metabolism of bacteria present in the oral cavity. These low pH substances dissolve the mineral components of enamel, cause tooth demineralization, and lead to decay or erosion damage with the irreversible loss of dental hard tissues and the necessity of their reconstruction. The range of dental materials intended for dental tissue reconstruction is extensive. Dental amalgam can be mechanically applied into the strongly stressed lateral segments of teeth. The use of amalgam is, however, in decline, with the possible health risks attributed to it, coupled with the need to extensively prepare tooth tissue promoting a shift towards using aesthetically and biologically favourable dental ceramic and polymeric materials instead. Current developments also concentrate on these materials to reinforce this, with polymeric composite materials based on methacrylates with varying amounts of inorganic fillers at the forefront. These materials are distinguished by their good mechanical and aesthetic properties and wear resistance. However, polymerization shrinkage and a strong hydrophobic nature does not allow for their direct bonding to hard dental tissues. Risks associated with the release of residual free monomers from the structure to the environment, which may cause health complications, mainly allergic reactions in sensitive individuals, have been monitored recently. Further development in the field of composite materials aims to reduce or completely eliminate these negatives.